Investigating the anti-bioadhesion properties of short, medium chain length, and amphiphilic polyhydroxyalkanoate films - Alexandra Guennec; Eric Balnois; Antoine Augias; Mama Aïssata Bangoura; Cédric Jaffry; Christelle Simon-Colin; Valérie Langlois; Fabrice Azemar; Guillaume Vignaud; Isabelle Linossier; Fabienne Faÿ; Karine Vallée-Réhel (Biofouling, 2024)

Pollution assessment around a big city in West Africa reveals high concentrations of microplastics and microbiologic contamination - Amidou Sonko; Patrice Brehmer; Guillaume Constantin de Magny; Gaël Le Pennec; Bissoume Sambe Ba; Ousmane Diankha; Mamadou Fall; Isabelle Linossier; Maryvonne Henry; Issa N’Diaye; Saliou Faye; Yoba Kande; et al. (Regional Studies in Marine Science, 2023)

Assessment of the global toxicity of marine sediments from the Dakar peninsula (Senegal, West Africa) - Amidou Sonko; Dalyal Copin; Patrice Brehmer; Cheikh Diop; Guillaume Constantin De Magny; Mamadou Fall; Yoba Kande; Patricia Moulin; Naby Souleymane Faye; Saliou Faye; Isabelle Linossier; Gaël Le Pennec (Environmental Monitoring and Assessment, 2023)

Temperate and tropical coastal waters share relatively similar microbial biofilm communities while free‐living or particle‐attached communities are distinct - Elisa Catão C. P.; Thomas Pollet; Cédric Garnier; Raphaëlle Barry‐Martinet; Karine Rehel; Isabelle Linossier; Alina Tunin‐Ley; Jean Turquet; Jean‐François Briand (Molecular Ecology, 2021)
Free‐living (FL) marine microbial communities differ from those attached to particles (PA). Likewise, biofilms (B) colonizing artificial surfaces, including plastics or ship hulls, hardly resemble their planktonic surroundings. However, few studies have examined the effect of the environment on these lifestyles and on the source of organisms colonizing marine surfaces. Using 16S rRNA gene metabarcoding, we identified specificities of marine prokaryotic community lifestyles (FL, PA or B) sampled in three coastal polluted locations with dissimilar environmental conditions: the North‐Western Mediterranean Sea and the Atlantic and Indian Oceans. Biofilms developed over polyvinyl chloride (PVC) were found to be significantly different from FL or PA collected during the immersions. Alpha‐diversity increased from FL to PA and to B, illustrating the integrative aspect of the latter, with little proportion of operational taxonomic units shared with the first two. Beta‐diversity clustered first the lifestyles and then the sites. FL and PA were more affected by water quality, especially by trace metal contamination, whereas B were as sensitive to trace metals as to nutrients. Although biofilms should be supplied by the planktonic (ultra) rare biosphere, source tracking could only detect small contributions of FL or PA taxa to B communities.

Bacteria and diatom resistance of silicones modified with PEO-silane amphiphiles - Melissa L. Hawkins; Fabienne Faÿ; Karine Réhel; Isabelle Linossier; Melissa A. Grunlan (Biofouling, 2014)

Effect of biofilm age on settlement of Mytilus edulis - Nicolas Toupoint; Vani Mohit; Isabelle Linossier; Nathalie Bourgougnon; Bruno Myrand; Frédéric Olivier; Connie Lovejoy; Réjean Tremblay (Biofouling, 2012)

Booster biocides and microfouling - Fabienne Faÿ; Isabelle Linossier; David Carteau; Alexandra Dheilly; Alla Silkina; Karine Vallée-Réhel (Biofouling, 2010)